Pengaruh Brand Image Terhadap Keputusan Pembelian Konsumen Produk Body Care Herborist di Sidoarjo - Risqy Maudy Inayah; Dhinda Lintang Cahya Gumilang; Zahra Nur Annisa; Nindya Kartika Kusmayati; Noneng R. Sukatmadiredja (Faculty of Social and Political Science, 2024)
This study seeks to assess how the brand image of Herborist body care products impacts consumers' purchasing choices. Brand image encompasses perceptions of product quality, safety, cleanliness, and effectiveness, all of which are significant factors influencing consumer preferences. Employing a quantitative approach, this study collected data through online questionnaires distributed via Google Form, with a sample size of 43 respondents. The findings of this research were demonstrated to be valid and reliable, meeting assumptions of normality and being free from heteroscedasticity and autocollinearity. A simple linear model Y = -0.733 + 0.852X + e was derived from the data, indicating that brand image (X) significantly affects purchasing decisions. To maintain or enhance purchasing decisions, companies must continually refine their marketing strategies to ensure effectiveness and yield positive outcomes in influencing consumer behavior.